Analysis of errors of HH-method of measuring the distance to the source of thunderstorm - Кораблев, А. В.; Яновский, Ф. И. (Proceedings of National Aviation University (archive), 2000)
Analyzed by mathematical and statistic modulation are the errors of HH-method of airborne thunderstorm telemetry. Received are quantitative error estimation of the considered method and the ways of increasing its precision are proposed